Neutrophil to lymphocyte and platelets to lymphocyte ratios as predictive factors of sepsis mortality - Vélez Páez, Jorge Luis (2019)
Background: Although there are several methods to assess the severity and mortality of sepsis based on scales and biomarkers, not all are available in health institutions for their cost Objective: To determine whether neutrophil / lymphocyte and platelet / lymphocyte indices are adequate predictors of severity and mortality in patients with sepsis and septic shock. Methods: Analytical observational study in 149 patients with sepsis and septic shock at the Hospital Docente de Calderón, Quito. Diagnosis of sepsis and septic shock according to SEPSIS 3 criteria, and its severity by means of Sequential Organic Failure Assessment (SOFA) and Acute Physiology and Chronic Health II (APACHE II). Indices between neutrophils-lymphocytes (INL) and platelets-lymphocytes (IPL) were calculated. The predictive mortality range of each index was established using adjusted Odd radios (multiple logistic regression) and areas under the curve (AUC) ROC (Receiver Operating Characteristic). Results: The APACHE II median was 17 ± 7 points, the SOFA median was 8 ± 4 points, and the mortality rate was 33.6%. Regarding mortality, INL with a cut-off point of ≥13.2 presented OR =1.03, AUC of 0.53, sensitivity of 47.1%, and specificity of 48.4%. IPL with a cut-off point of ≥221.8 presented an OR =1.002 (95% CI 0.999-1.003), AUC of 0.56, sensitivity of 47.1%, and specificity of 48.4% Conclusions: Neutrophil / lymphocyte and platelet / lymphocyte indices are tests with low predictive power to assess the severity and mortality of patients with sepsis and septic shock.